Touch Avoidance with Close People and Strangers: Effects of Gender, Sexual Orientation, and Relationship Status - Francesco Bruno; Chloe Lau; Carlotta Tagliaferro; Lena C. Quilty; Francesca Chiesi (MDPI AG, 2023)
Human contact through physical touch is a core element in social bonding, which facilitates psychosocial well-being. Touch avoidance is an individual disposition that may prevent individuals from engaging in or benefiting from physical touch. The present study recruited 450 Italian participants (51.1% female) with a mean age of 32.2 ± 13.5 to complete a battery of demographic questionnaires and the Touch Avoidance Questionnaire (TAQ). Individuals who were single and reporting same-sex attraction avoided touch with family more often than their coupled counterparts or those reporting opposite-sex attraction. Moreover, males reporting same-sex attraction avoided touch with a potential partner more frequently. When comparing sex differences, women reported greater touch avoidance with opposite-sex friends more frequently, while males avoided touch with same-sex friends more frequently. Individuals reporting opposite-sex attraction reported greater touch amongst same-sex friends. Single males avoided touch with same-sex friends more frequently than those in a relationship. Overall, this contribution reflects the individual differences related to social touch avoidance with respect to sex, relationship status, and sexual orientation in an Italian sample.